Effectiveness of Non-Surgical Procedures for the Treatment of Black Triangle Cases in the Aesthetic Zone on the Height of the Interdental Papilla: Narrative Review - Yusuf, Muhammad; Syaify, Ahmad; Karina, Vincensia Maria (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: The black triangle is a cervical embrasure to the proximal contact that is not filled with gingival tissue. Until, the treatment of black triangle cases has evolved to offer non-surgical procedures such as hyaluronic acid injection, Injectable Platelet Rich Fibrin (i-PRF), and photobiomodulation therapy. Various studies have also reported the use of hyaluronic acid, i-PRF and photobiomodulation therapy to increase the height of the interdental papillae.Method: Literature searches were carried out systematically from various international databases such as PubMed, ScienceDirect, Google Scholar, and Semantic Scholar. The literature selection stages are carried out through the process of identifying articles, screening, and fulfilling inclusion criteria. A total of 52 articles were published in 2012 – 2022 and have met the criteria for data extraction examination of various clinical parameters from the black triangle case.Result: The results of the review showed that the use of hyaluronic acid injection, i-PRF and photobiomodulation therapy showed significant treatment results in cases of black triangle class I and II. Conclusion: It was reported that the non-surgical procedure for the treatment of black triangle cases produce better result and predictable results, an easy technique, more effective time than surgical procedures and reduced discomfort and met the aesthetic demands of patients based on clinical parameters after 6 month injection.